1982
DOI: 10.1038/icb.1982.4
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF DIETARY RESTRICTION, ADRENALINE, HYDROCORTISONE AND SURGERY ON THE RATES OF DEATH OF 125IUdR‐LABELLED, INTRAVENOUSLY INJECTED TUMOUR CELLS IN THE LUNGS OF MICE

Abstract: Summao'. Dietary restriction, adretiiiline. hydrocortisone or surgery reduced the rate at which pulmonarily arresied '-''IUdR-labelled murine lumour cells were lost within 7 h of intravenous (i.v.) injection. Mice that had been adrenalectomised 10 days previously showed a normal intrapiilmonary tumour cell loss rate wilh furiher surjjery reducing this rate to approximately half that observed in normal mice thai had been subjected to surgery. Thus, although it is likely that adrenal hormones play an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As the pulmonary loss of radioactivity within 24h of i.v. injection has been clearly shown to be a consequence of the intravascular death of arrested tumour cells (Bishop & Donald, 1979;Talmadge et al, 1980;Bishop et al, 1982), it was concluded in the above studies that the intravascular death of i.v. injected tumour cells was at least in part due to NK cell-mediated killing of the tumour cells.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As the pulmonary loss of radioactivity within 24h of i.v. injection has been clearly shown to be a consequence of the intravascular death of arrested tumour cells (Bishop & Donald, 1979;Talmadge et al, 1980;Bishop et al, 1982), it was concluded in the above studies that the intravascular death of i.v. injected tumour cells was at least in part due to NK cell-mediated killing of the tumour cells.…”
mentioning
confidence: 99%
“…Furthermore, the rate of intravascular tumour cell death following i.v. injection has been shown to be influenced by a wide variety of host treatments (Bishop et al, 1982). It is possible that multiple host factors, perhaps including NK cells to a minor extent, may be involved in the intravascular death of i.v.…”
mentioning
confidence: 99%
See 2 more Smart Citations